2021
DOI: 10.1080/25741292.2021.1917173
|View full text |Cite
|
Sign up to set email alerts
|

Policy labs challenges in the public sector: the value of design for more responsive organizations

Abstract: Design has emerged as a discipline equipped to tackle the complex problems of the 21st century, primarily for its human-centered and experimentation approach and participative qualities. Through the discussion of a case study of a government design lab, formerly inside the Finnish Immigration Service, the question of how design can help public sector organizations better respond to their pressing needs is addressed, in an attempt to explore the value of design as it is being used by the increasing population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
7
0
3
Order By: Relevance
“…Olejniczak et al (2020) found that it was unclear if policy labs were "effectively feeding their solutions into the actual policymaking and policy implementation process" (p. 104). Komatsu et al (2021) also made similar criticisms. Finally, while some publications highlighted the evaluation of PILs, there was very little evidence of labs playing a role in formal policy evaluations or the policy cycle.…”
Section: State Of the Policy Innovation Lab Scholarshipmentioning
confidence: 75%
See 2 more Smart Citations
“…Olejniczak et al (2020) found that it was unclear if policy labs were "effectively feeding their solutions into the actual policymaking and policy implementation process" (p. 104). Komatsu et al (2021) also made similar criticisms. Finally, while some publications highlighted the evaluation of PILs, there was very little evidence of labs playing a role in formal policy evaluations or the policy cycle.…”
Section: State Of the Policy Innovation Lab Scholarshipmentioning
confidence: 75%
“…This paper is the fourth study of the lab, an ongoing process of design experiments supported by the Finnish government (see Kantola 2019;Kokki 2018;Swan 2018 in Appendix 1). Komatsu et al (2021) argue that design culture is essential for meaningfully transforming an organization through human-centered design and co-creation (See O'Flynn 2007). Readers have the opportunity to experience the details of the design process and the improvements made in a 2017 pilot to improve immigrant-related services.…”
Section: Special Issue Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…O principal objetivo dos laboratórios de políticas públicas é promover o atendimento à sociedade com a entrega de resultados em uma ampla gama de áreas, tais como: governança, educação, saúde, imigração e emigração, habitação, transporte, segurança pública, transformação social, sustentabilidade, entre outras (UNCETA; BARANDIARAN e RES- TREPO, 2019;BROCK, 2021;KOMATSU et al, 2021, LEWIS, 2021.…”
Section: Laboratórios De Inovação Em Políticas Públicasunclassified
“…In this sense, when reviewing the literature, concepts related to SIL were found: fab labs (STACEY, 2014), citizen laboratories, living laboratories, virtual laboratories, social innovation laboratories, innovation laboratories, as well as urban living laboratories or urban laboratories (YAÑEZ-FIGUEROA; RAMÍREZ-MONTOYA; GARCÍA-PEÑALVO, 2016). For this article, SIL are considered as a sample of communities of practice (KOMATSU et al, 2021) that seek to project actions for the common good (EJDERYAN et al, 2019) by creating spaces for the interaction (DEFILA; DI GIULIO, 2020) of various disciplines (BARTH;LANG;MICHELSEN, 2019) for SCK that can be used in reality (WILLIAMSON, 2015).…”
Section: Social Innovation Laboratories (Sil)mentioning
confidence: 99%